Combination Therapy of All-Trans Retinoic Acid With Ursodeoxycholic Acid in Patients With Primary Sclerosing Cholangitis: A Human Pilot Study. Issue 2 (February 2017) - Assis, David N.; Abdelghany, Osama; Cai, Shi-Ying; Gossard, Andrea A.; Eaton, John E.; Keach, Jill C.; Deng, Yanhong; Setchell, Kenneth D.R.; Ciarleglio, Maria; Lindor, Keith D.; Boyer, James L.
Abstract : Goals: To perform an exploratory pilot study of all-trans retinoic acid (ATRA) combined with ursodeoxycholic acid (UDCA) in patients with primary sclerosing cholangitis (PSC). Background: PSC is a progressive disorder for which there is no accepted therapy. Studies in human hepatocyte cultures and in animal models of cholestasis indicate that ATRA might have beneficial effects in cholestatic disorders. Study: ATRA (45 mg/m 2 /d, divided and given twice daily) was combined with moderate-dose UDCA in patients with PSC who had incomplete response to UDCA monotherapy. The combination was administered for 12 weeks, followed by a 12-week washout in which patients returned to UDCA monotherapy. We measured alkaline phosphatase (ALP), alanine aminotransferase (ALT), bilirubin, cholesterol, bile acids, and the bile acid intermediate 7α-hydroxy-4-cholesten-3-one (C4) at baseline, week 12, and after washout. Results: Fifteen patients completed 12 weeks of therapy. The addition of ATRA to UDCA reduced the median serum ALP levels (277±211 to 243±225 U/L, P =0.09) although this, the primary endpoint, did not reach significance. In contrast, median serum ALT (76±55 to 46±32 U/L, P =0.001) and C4 (9.8±19 to 7.9±11 ng/mL, P =0.03) levels significantly decreased. After washout, ALP and C4 levels nonsignificantly increased, whereas ALT levels significantly increased (46±32 to 74±74, P =0.0006), returning to baseline. Conclusions: In this human pilot study, the combination of ATRA and UDCA did not achieve the primary endpoint (ALP); however, it significantly reduced ALT and the bile acid intermediate C4. ATRA appears to inhibit bile acid synthesis and reduce markers of inflammation, making it a potential candidate for further study in PSC (NCT 01456468).